Regulatory policy scan of Bulgaria Promoting a sound regulatory framework for citizen well-being and economic growth (OECD Public Governance Policy Papers, 2022)
The Regulatory Policy Scan of Bulgaria assesses the country's regulatory management capacity by taking stock of regulatory policies, institutions and tools, describing trends and recent developments, and identifying gaps in relation to good practices. Improving the entire regulatory policy cycle will ensure that regulations are developed on a foundation of solid evidence and public participation and designed to enhance citizens' security, health and wellbeing at a reasonable cost. Together with the Centre of Government Scan and Public Integrity Scan this policy paper is a part of the governance scan series drafted in the framework of the "Driving Public Administration Reform Forward" project funded by the European Commission's Directorate-General for Structural Reform Support